Essere e Tempo novanta anni dopo attualità e inattualità dell'analitica esistenziale - Anna Pia Ruoppo (Scuola di Scienze Umane e Sociali. Quaderni, 2019)
Divided into three sections: the existential analytics between neokantism, phenomenology and hermeneutics; ethics, praxis, politics starting from Being and Time; confrontations, deepening, perspectives, this collective volume, inspired by "a hermeneutics of Sachlichkeit", tries to offer a balance on the actuality and unactuality of existential analytics ninety years after publication of Being and Time. Authors from different contexts present the existential analytics in the historical and theoretical context of its first formulation, question the complex problem of a possible praxis or a possible ethics within Heideggerian ontology and measure the impact of existential analytics on contemporary thinkers. It emerges how, despite all the problems and open questions, "the debt of contemporary thought to Heidegger is great and how important it is to preserve the legacy of his thought and the tradition in which it is placed, beyond any false alternative between naive apologetics and radical criticism".